Đáp án+Giải thích các bước giải:
a)
`h(x)=f(x)+g(x)`
`=(x^4+x^3-3x^2+2x-9)+[x^2(2-x^2)-(x-8)]`
`=x^4+x^3-3x^2+2x-9+2x^2-x^4-x+8`
`=(x^4-x^4)+x^3+(2x^2-3x^2)+(2x-x)+(8-9)`
`=x^3-x^2+x-1`
Bậc: `3`
Hệ số cao nhất: `1`
Hệ số tự do: `-1`
b)
Cho `h(x)=0`
`->x^3-x^2+x-1=0`
`->(x^3-x^2)+(x-1)=0`
`->x^2(x-1)+(x-1)=0`
`->(x^2+1)(x-1)=0`
`->x^2+1=0` hoặc `x-1=0`
`->x^2=-1` (loại vì `x^2>=0`) hoặc `x=1`
Vậy nghiệm của đa thức `h(x)` là `x=1`
c)
`h(x)-k(x)=1/2x^2`
`->x^3-x^2+x-1-k(x)=1/2x^2`
`->k(x)=x^3-x^2+x-1-1/2x^2`
`->k(x)=x^3-(x^2+1/2x^2)+x-1`
`->k(x)=x^3-3/2x^2+x-1`
Vậy `k(x)=x^3-3/2x^2+x-1`